Fluorescent fiber-based identification of incipient discharges in liquid nitrogen. (December 2021) - Naveen, Janjanam; Sarathi, R.; Srinivasan, B.
Highlights: Variety of fluorescent fibers with different absorption/emission characteristics were used for identification of corona and surface discharges, and we find that a particular type of fluorescent fiber is more sensitive to identify discharges in liquid nitrogen insulation than UHF technique. The characteristic spectral content of the fluorescent signal due to corona and surface discharge activity formed in liquid nitrogen is observed up to 3 MHz. Enhancement in the magnitude of fluorescent signal/UHF signal is observed for increase in applied voltage beyond the corona inception voltage (CIV). Also, it is observed that while reducing the applied voltage, the corona activity quenches at much lower voltage than the inception voltage. It is observed that 3 wt% of nano mgo added GFRP epoxy nanocomposite sample exhibits enhanced surface discharge inception voltage (SDIV) compared to samples with other concentrations of mgo and that the SDIV is lower for AC voltage when compared with the DC voltage conditions. A phase-resolved partial discharge (PRPD) analysis was also carried out to identify corona and surface discharge activity using fluorescent fiber sensor and with UHF sensor. From the PRPD studies, it is observed that the corona discharge occurs near the peak magnitude whereas surface discharge is observed at the rising part of AC voltage. Abstract: Identification of incipient discharges is a major challenge in liquid nitrogenbased super-conducting power apparatus. In the present study, a variety of fluorescent fibers with different absorption/emission characteristics were used for the identification of corona and surface discharges, and we find that a particular type of fluorescent fiber is more sensitive to identify discharges in liquid nitrogen insulation than the UHF technique. Enhancement in the magnitude of fluorescent signal/UHF signal is observed for an increase in applied voltage beyond the corona inception voltage (CIV). Also, it is observed that while reducing the applied voltage, the corona activity quenches at a much lower voltage than the inception voltage. No characteristic variation in rise time or the fall time of the fluorescent signal is observed on corona inception and due to discharges at higher voltages. The corona inception voltage is least for AC voltage conditions, and slightly higher inception voltage is observed for positive DC and negative DC voltage conditions. Different weight percentages of MgO doping in GFRP nanocomposites are prepared and used in the surface discharge studies. It is observed that the 3 wt% sample exhibits enhanced surface discharge inception voltage (SDIV) compared to samples with other doping concentrations and that the inception voltage is lower for AC voltage when compared with the DC voltage conditions. The characteristic spectral content of the fluorescent signal due to corona and surface discharge activity is observed up to 3 MHz. A phase-resolved partial discharge (PRPD) analysis was also carried out to identify corona and surface discharge activity using fluorescent fiber sensor and with a UHF sensor. From the PRPD studies, it is observed that the corona discharge occurs near the peak magnitude whereas surface discharge is observed at the rising part of AC voltage.